Disequilibrium of Flavonol Synthase and Dihydroflavonol-4-Reductase Expression Associated Tightly to White vs. Red Color Flower Formation in Plants - Luo, Ping; Ning, Guogui; Wang, Zhen; Shen, Yuxiao; Jin, Huanan; Li, Penghui; Huang, Shasha; Zhao, Jian; Bao, Manzhu (Frontiers in Plant Science, 2016)
Flower colour is the main character throughout the plant kingdom. Though substantial information exists regarding the structural and regulatory genes involved in anthocyanin and flavonol biosynthesis, little is known that what make a diverse white versus red color flower in natural species. Here, the contents of pigments in seven species from varied phylogenetic location in plants with red and white ﬂowers.were determined. Flavonols could be detected in red and white ﬂowers, but anthocyanins were almost undetectable in the white cultivar. Comparisons of expression patterns of gene related to the flavonoid biosynthesis indicated that disequilibrium expression of flavonol synthase (FLS) and dihydroflavonol-4-reductase (DFR) genes determined the accumulation of flavonols and anothcyanins in both red and white flowers of seven species. To further investigate the role of such common regulatory patterns in determining flower color, FLS genes were isolated from Rosa rugosa (RrFLS1), Prunus persica (PpFLS) and Petunia hybrida (PhFLS), and DFR genes were isolated from Rosa rugosa (RrDFR1) and Petunia hybrida (PhDFR). Heterologous expression of the FLS genes within tobacco host plants demonstrated conservation of function, with the transgenes promoting flavonol biosynthesis and inhibiting anthocyanin accumulation, so resulting in white ﬂowers. Conversely, overexpression of DFR genes in tobacco displayed down-regulation of the endogenous NtFLS gene, and the promotion of anthocyanin synthesis. On this basis, we propose a model in which FLS and DFR gene-products compete for common substrates in order to direct the biosynthesis of flavonols and anthocyanins, respectively, thereby determining white versus red coloration of flowers.